2016
DOI: 10.1016/j.ajpath.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Inhibition Prevents Tumor Necrosis Factor-α–Induced Apoptosis and Promotes Necrotic Cell Death in Mouse Hepatocytes in Vivo and in Vitro

Abstract: How different cell death modes and cell survival pathways cross talk remains elusive. We determined the interrelation of apoptosis, necrosis, and autophagy in tumor necrosis factor (TNF)-a/actinomycin D (ActD) and lipopolysaccharide/D-galactosamine (GalN)-induced hepatotoxicity in vitro and in vivo. We found that TNF-a/ActD-induced apoptosis was completely blocked by a general caspase inhibitor ZVADfmk at 24 hours but hepatocytes still died by necrosis at 48 hours. Inhibition of caspases also protected mice ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Consistent with previous reports, treatment of mice with a pan-caspase inhibitor effectively protected against apoptosis during the early injury phase in the galactosamine/endotoxin model, but even with this sustained inhibition of caspase activity, cells eventually undergo massive necrosis 24 hours after the initial treatment [22]. Although caspase inhibition prevented RIP1 and RIP3 degradation, this cell death was independent of traditional necroptosis.…”
Section: Caspase Inhibition – Physiology Pharmacology and Beyondsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous reports, treatment of mice with a pan-caspase inhibitor effectively protected against apoptosis during the early injury phase in the galactosamine/endotoxin model, but even with this sustained inhibition of caspase activity, cells eventually undergo massive necrosis 24 hours after the initial treatment [22]. Although caspase inhibition prevented RIP1 and RIP3 degradation, this cell death was independent of traditional necroptosis.…”
Section: Caspase Inhibition – Physiology Pharmacology and Beyondsupporting
confidence: 88%
“…Although caspase inhibition prevented RIP1 and RIP3 degradation, this cell death was independent of traditional necroptosis. Both RIP3-deficient mice and wild type animals treated with the RIP1 inhibitor necrostatin-1 were not protected and had a poorer inflammatory profile, indicating that activation of the TNF-α pathway may have additional mechanisms of injury in vivo that also escape caspase inhibition [22]. These findings clearly demonstrate differential effects of caspase inhibitors when used short-term versus more long-term or even chronically.…”
Section: Caspase Inhibition – Physiology Pharmacology and Beyondmentioning
confidence: 99%
“…Th17 cells gen, whereas the downregulated cluster was enriched for genes involved in lipid metabolism ( Figure 2E). Consistently, mRNA expression of genes involved in liver fibrosis, including Col1a1, Acta2, Tgfb1, and Mmp13, and hepatic inflammation, including Previous studies have demonstrated that treatments of primary hepatocytes with a combination of palmitic acid (PA) and TNF-α (PA/TNF-α) robustly triggered cell death that mimics NASHinduced liver injury (21,37). To investigate whether Nrg4 plays a direct role in the regulation of hepatocyte death, we treated primary hepatocytes transduced with GFP or ErbB4 adenovirus with PA/TNF-α.…”
Section: Resultsmentioning
confidence: 90%
“…These data agree with an earlier report showing caspase-3—independent hepatocyte necrosis as the predominant mechanism of ConA-induced liver damage in vivo . 39 Although several TUNEL-positive hepatocytes found in ConA-treated mice might suggest involvement of other caspases, as significant inhibition of ConA-induced apoptosis was observed by blocker of caspase-1—like protease YVADcmk, 46 a recent report by Ni et al 47 demonstrated that TUNEL-positive cells could be either apoptotic or necrotic. Because ConA-treated HSCs induced apoptosis but not necrosis in vitro (Figure 5 and Supplemental Figure S8), it is conceivable that the caspase cascade is activated earlier after ConA challenge in vivo , and with increased generation of mediators of cell damage by infiltrating cells and ATP depletion, necrosis predominates as a major mechanism of cell death.…”
Section: Discussionmentioning
confidence: 99%